Coherent photoproduction of ρ0 vector mesons in ultra-peripheral Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; López, Jorge; Martin, Nicole Alice; et al. (Journal of high energy physics, 2020)
Cross sections for the coherent photoproduction of ρ0 vector mesons in ultra-peripheral Pb-Pb collisions at sNN$$ \sqrt{{s}_{NN}} $$= 5.02 TeV are reported. The measurements, which rely on the π+π− decay channel, are presented in three regions of rapidity covering the range |y| < 0.8. For each rapidity interval, cross sections are shown for different nuclear-breakup classes defined according to the presence of neutrons measured in the zero-degree calorimeters. The results are compared with predictions based on different models of nuclear shadowing. Finally, the observation of a coherently produced resonance-like structure with a mass around 1.7 GeV/c2 and a width of about 140 MeV/c2 is reported and compared with similar observations from other experiments.